Psychoneuroimmunology: a cross-cultural, biopsychosocial study of the role of perceived social support for people living with HIV/AIDS - Cortes Rojas, Aaron (2011)
Background: The immunological as well as the psycho-social impact, of living with HIV/AIDS transform HIV/AIDS into a multidimensional process. Stigma and discrimination against people living with HIV/AIDS (PLWHA) are proposed as hostile scenarios increasing hopelessness and reducing perceived and real social support affecting people’s health status. Peer support strategies are proposed as key factors for dealing with this scenario; additionally, socio-cultural variables may determine the provision and perception of social support. Objectives: To enhance the understanding of the process of living with HIV/AIDS and the role played by social support and to suggest cooperative strategies for dealing with stigma and discrimination against PLWHA to improve people’s health. Sample and method: Five studies were conducted studying 37 HIV positive members and non-members of peer support organisations (PSOs) in Chile and England; nine healthcare professionals working with PLWHA; and three spokes persons from PSOs of PLWHA from Romania, England and Chile. Results: PSOs of PLWHA, which reflect a cooperative strategy used by PLWHA to deal with stigma and self-provide social support, appear to play an important and underexplored role in PLWHAs’ health status; this relationship is also affected by socio-cultural characteristics. A measure of PSS was developed and theoretical analysis lead to a linkage with Maslow’s hierarchy of needs. Personality characteristics were found critical for the success of PNI based interventions. Conclusions: Living with HIV/AIDS involves psychological and social complications. PSOs are a powerful cooperative strategy improving quality of life and general health; however, further research is needed to establish the real impact of PSOs over HIV+ people. Implications: The peer-support strategy of PSOs is a powerful but underused clinical strategy. Healthcare teams and PLWHA may benefit from including this strategy if cooperative work is carried out with PSOs.